Hubungan Stress dan Obesitas dengan Gangguan Pola Menstruasi pada Remaja Siswi SMAN 1 Majene Tahun 2026 - Rasmawati Rasmawati; Nurfadhila Nurfadhila; Nur Anisafauziah; Sitti Harma (Jurnal Sains dan Kesehatan, 2026)
Background: Menstruation is a natural physiological process that indicates the functional maturity of the female reproductive system. Menstrual cycle disorders can be influenced by several factors, including stress and obesity. Stress may cause hormonal changes through the hypothalamic-pituitary axis, leading to decreased luteinizing hormone (LH) levels and menstrual irregularities. Obesity can also affect ovarian function and disrupt the menstrual cycle. Objective: To determine the relationship between stress and obesity with menstrual cycle disorders among female adolescents at SMAN 1 Majene in 2026. Methods: This study used an analytical observational design with a cross-sectional approach. Data on stress levels, obesity status, and menstrual cycle disorders were collected simultaneously from 84 female respondents. The chi-square test was used to analyze the relationships among variables. Results: The analysis showed a significant relationship between stress and menstrual cycle disorders (p = .006; α < .05). A significant relationship was also found between obesity and menstrual cycle disorders (p = .002; α < .05). Many obese respondents experienced irregular menstrual cycles. Conclusion: There is a significant relationship between stress and obesity with menstrual cycle disorders among female adolescents at SMAN 1 Majene.